Philosophical Narratives of Suffering: Nietzsche, Levinas, Weil and Their Cultural Roots - Elisa Aaltola (Finnish Anthropological Society, 2022)
The sort of meanings which suffering is depicted with influence both individual experiences of and social responses to it. In contemporary research, these meanings have been explored via mapping out individual narratives on illness and suffering, and by locating common typologies underlying them. Much less emphasis has been placed on philosophical narratives on suffering and the manner in which they both echo and strengthen culturally common Western meanings concerning human travails. The paper takes its impetus from here and examines three distinct philosophical narratives on suffering presented by Emmanuel Levinas, Friedrich Nietzsche, and Simone Weil. Moreover, it investigates the cultural influences behind them, ranging from Homeric tragedies to Medieval Christianity and Holocaust portrayals. The suggestion is that analysing philosophical narratives facilitates moral comparisons between the varieties of cultural meanings given to suffering. This, again, enables one to locate the societal and political consequences that narratives of suffering have on how we approach, for instance, vulnerability and disability.